COLLATERAL OPERATIONS OF BANKS IN TERMS OF EXISTENTIAL CRISES IN UKRAINE - SHELUDKO, Sergii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The paper presents results of the study on essence, types and features of collateral operations of Ukrainian banks in terms of existential crises. It is studied the legal interpretation of the essence of pledge, its own definition has been proposed. It is disclosed features of pledge as an instrument of securing bank loans, which consists in the ability to secure possible future claims, therefore its spread in bank lending is justified by the ability to cover not only the borrowed value, but also accrued interest, including at a variable (floating) rate. It is presented the author’s approach to the essence of collateral operation as a complex of interrelated bank’s actions aimed at establishing, terminating and realizing the right of pledge, the subject of which is property pledged to secure loans granted or received on the basis of concluded pledge agreements. It is substantiated the extraction of valuation, insurance, and monitoring collateral operations, which reflect the bank’s actions to implement the principles of the acceptance of security for clients’ credit debt, namely: the principle of fair valuation, the principle of preservation, and the principle of availability. It is analyzed the dynamics and structure of the aggregate collateral portfolio of Ukrainian banks within the available statistical base (since Q3 2017). It is concluded that the security of bank loans has deteriorated as a result of the reduction in the value of the pledged property against the background of an almost unchanged volume of the loan portfolio. It is substantiated the imbalance in the structure of the collateral portfolio, where more than 2/3 is constituted by various types of movable property and property rights, while real estate objects do not exceed 35%. It is noted a decrease in the productivity of bank lending against a weakening of the corresponding collateral coverage, which is confirmed by the low ratio of the value of the collateral to the volume of lending and the excessive liquidity of the banking system in Ukraine.